KESIAPSIAGAAN KOMUNITAS SEKOLAH DASAR INKLUSI DALAM MENGHADAPI BENCANA GEMPA BUMI DI YOGYAKARTA - Fika Nur Indriasari (Jurnal Keperawatan Notokusumo, 2017)
Background : Indonesia is located within a ring of fire and Yogyakarta is part of the area which has an earth quake potential. In 2006, a big earth quake was happened with impacted a lot of fatality, especially children and elderly. School disaster awareness is a primary key to protect children and young generation for save environtment to study from unexpected disaster. The achievement of disaster awareness in the school is very important because Indonesia is one of the country has high risk in natural disaster. Objective: To find out the readiness of inclution school to face an earthquake and parameters inclution school for an earthquake disaster. Method: The design of the research is cross sectional and the technique of sample collection with 30 respondents by quisioner and interview. Data analysis uses a descriptive analysis. Result: The readiness of teachers and staff within low category are 18 peoples (60%). The low rate of parameter for school inclution shows the readiness of school is still low. Conclution: The implementation of inclution school to face an earthquake is very important at the area with high risk in eartquake disaster. The parameter value in inclution school indicates the readiness is still low with 60% for the teacher and staff.